PENGARUH LUAS UNGKAPAN SUKARELA DAN ASIMETRI INFORMASI TERHADAP COST OF EQUITY CAPITAL - Sari, Felia Arienza; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of width of voluntary disclosure and asymmetric information to the cost of equity capital. The width of voluntary disclosure variable is measured by the Voluntary Disclosure Index (IPS)which consists of 33 disclosure items. Asymmetric information is measured by using bid-ask spread proxy and Cost of Equity Capital variable is done by using Ks formula. The samples are property and real estate companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2104 periods and these companies have been selected by using purposive sampling. There are 34 companies with a 3 year periods so 102 samples have been obtained. This research has been done by usingthe data from the STIESIA Indonesia Stock Exchange Corner and Indonesia Stock Exchange website. The analysis method has been carried out by using multiple regressions model.The results of this research shows that the expression of voluntary has an influenceto the cost of equility capital whereasasymmetric information does not have any influenceto the cost of equility capital.Keywords: Voluntary expression, asymmetric information, cost of equality capital.